2018
DOI: 10.5539/ijps.v10n2p41
|View full text |Cite
|
Sign up to set email alerts
|

The Abbreviated Psychopathy Measure (APM): Two Pilot Studies of a Brief Measure of Psychopathy Traits

Abstract: Two studies were undertaken to examine preliminary construct validity of a newly developed, abbreviated measure of psychopathy. The Abbreviated Psychopathy Measure (APM) is a 33-item inventory that is closely modeled on the Triarchic Psychopathy Measure (TriPM; Patrick, 2010), with a new and more parsimonious set of items. Analyses in Study 1 (N = 126) found that the Boldness, Meanness, and Disinhibition scales of the APM had high internal consistency reliabilities and were highly correlated with their counter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 41 publications
2
5
0
Order By: Relevance
“…Whether this might hold true for APM-2 Meanness remains to be seen. The current finding is also consistent with the previous finding (Semel, 2018) that APM Meanness was strongly associated (negatively) with Agreeableness as assessed with the Big Five Inventory (BFI; John, Donahue, & Kentle, 1991). Very low agreeableness/very high antagonism is considered by some (see Miller & Lynam, 2015) to be most essential to the construct of psychopathy.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Whether this might hold true for APM-2 Meanness remains to be seen. The current finding is also consistent with the previous finding (Semel, 2018) that APM Meanness was strongly associated (negatively) with Agreeableness as assessed with the Big Five Inventory (BFI; John, Donahue, & Kentle, 1991). Very low agreeableness/very high antagonism is considered by some (see Miller & Lynam, 2015) to be most essential to the construct of psychopathy.…”
Section: Discussionsupporting
confidence: 91%
“…Very low agreeableness/very high antagonism is considered by some (see Miller & Lynam, 2015) to be most essential to the construct of psychopathy. Similar to the finding by Semel (2018), Hall et al (2014) found that PPI-Meanness was a very robust…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations